Poskolonialisme dan Ekologi Pascakolonial: Sebuah Tinjauan Pustaka - Nasrullah, Nasrullah; Pawi, Awang Azman Awang; Hassan, Ummi Hani Abu (Journal of International and Local Studies, 2025)
Postcolonialism and postcolonial ecology are two concepts that emerge from their interconnectedness. Postcolonialism itself arises from the intersection of poststructuralist and neo-Marxist thought, while postcolonial ecology originates from the intersection of ecological studies (or ecocriticism) and postcolonial studies. The relationship between these fields further enriches the analysis of the complex socio-cultural dynamics present in today's society. This paper aims to contribute to the existing literature on postcolonial and ecological studies by introducing an ecological approach that also addresses the influence of colonial ideologies and practices from the past, which continue to have an impact today. The hope is that this literature review will heighten postcolonial awareness, particularly within the realm of ecological studies, and serve as a valuable analytical tool for understanding the impacts of climate change that have been increasingly discussed and studied in recent times.